2007
DOI: 10.1038/bdj.2007.75
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser use in dentistry

Abstract: • Low-level, non-cutting lasers are commonly used in many areas of general medicine and veterinary practice.• Their use in treating pathology is based on photobiostimulation, in which laser energy is absorbed by inter-and intra-cellular targets, resulting in a secondary stimulation of tissue healing mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 54 publications
2
55
0
5
Order By: Relevance
“…However, some studies have shown useful findings in treatment of dentin hypersensitivity, temporomandibular joint disorders, inferior alveolar nerve paraesthesia resulting from third molar surgery, sagittal osteotomy, trigeminal neuralgia, labial herpes, aphthous ulcers and post-chemotherapy and ray inflammation. [7][8][9][10][11][12] As there are conflicting findings regarding the effectiveness of low-level laser therapy (LLLT) and the importance of controlling third molar surgery's complications, this study aimed to assess the effect of LLLT on pain, swelling and maximum mouth opening in patients undergoing third molar surgery. In this study, we increased the number and variety of studied groups in order to reduce the error rate, in comparison to former researches.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown useful findings in treatment of dentin hypersensitivity, temporomandibular joint disorders, inferior alveolar nerve paraesthesia resulting from third molar surgery, sagittal osteotomy, trigeminal neuralgia, labial herpes, aphthous ulcers and post-chemotherapy and ray inflammation. [7][8][9][10][11][12] As there are conflicting findings regarding the effectiveness of low-level laser therapy (LLLT) and the importance of controlling third molar surgery's complications, this study aimed to assess the effect of LLLT on pain, swelling and maximum mouth opening in patients undergoing third molar surgery. In this study, we increased the number and variety of studied groups in order to reduce the error rate, in comparison to former researches.…”
Section: Introductionmentioning
confidence: 99%
“…However, the long healing time and postsurgical high level pain of this treatment may cause patient discomfort with conventional gingivectomy procedures. 4 Pain is one of the most important and common postoperative complications, that may intolerance on the patient for the surgical quality. 5 Other important side effect for conventional gingivectomy 7 method into two groups of control (10 subjects treated with the conventional surgery) and experimental (10 subjects treated with diode laser gingivectomy).…”
mentioning
confidence: 99%
“…It is believed that the light may be absorbed by chromophores in the cells (23), providing an increase in the activation of the cytochrome c oxidase pathway (6,16,20). This would generate an increase in the production of ATP and, consequently, induce cell proliferation (5,13).…”
Section: Discussionmentioning
confidence: 99%
“…The main overall mechanism of action of this therapy is the stimulation of cell metabolism and tissue repair, thus favoring a more effective and rapid response of the tissue or organ exposed to an aggression (4). It has been demonstrated that irradiation with red and infrared lights improves the ATP synthesis and stimulates cell proliferation (5,6). However, the mechanism of action of this therapy is still not completely elucidated (3).…”
Section: Introductionmentioning
confidence: 99%